An Analysis English and Sundanese Polite Utterances : Descriptive Study to Sundanese of English Department - zulaikah, zulaikah; Nisa , Khoirun; Hadziq Fikri , Arief (Darussalam English Journal (DEJ), 2024)
This study aims to determine the used of polite utterances in English and Sundanese which has three components and their causal factors. This research is a qualitative descriptive study with a pragmatic approach. The data of this study were obtained by referring to the method of conversational observation techniques, and recording techniques. The data collection technique was a test consisting of three components of polite utterances in English and Sundanese. The data collection technique is a test consisting of polite utterances, namely: speech acts, politeness, pragmatics, Basa Loma, Basa Hormat keur ka Sorangan, Basa Hormat keur ka Batur and the data analysis is data reduction, data presentation and conclusion drawing/verification. Based on the results of the study, the writer found that the used of polite utterances in English and Sundanese by students of Sundanese ethnicity in the English education study program at Nurul Huda University was the used of polite utterances which still used Basa Loma and at least conversations which included pragmatics with test results used polite utterances. 125 from 9 respondents and for the results of the observation used tests only 2 from 9 respondents